2019
DOI: 10.1002/elan.201900068
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Detection of Zika Virus in Biological Samples: A Step for Diagnosis Point‐of‐care

Abstract: This work describes an electrochemical genosensor for detection of genomic RNA of Zika virus in real samples of infected patients, using a new platform based on graphite electrodes modified with electrochemically reduced graphene oxide and polytyramine‐conducting polymer. The developed genosensor was suitable for differentiation between samples of healthy and infected patients with Zika virus by differential pulse voltammetry, detecting up to 0.1 fg/mL (1.72 copies/mL), showing good stability (about 60 days), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 38 publications
(31 reference statements)
0
22
0
Order By: Relevance
“…The LOD reached 0.1 fg mL −1 (1.72 copies mL −1 ). The advantages of this method were rapid analysis (20 min), a reliable response even after 60 days of storage and the possibility of miniaturization ( Moço et al, 2019 ).…”
Section: Graphene-based Materials In Virus Sensingmentioning
confidence: 99%
“…The LOD reached 0.1 fg mL −1 (1.72 copies mL −1 ). The advantages of this method were rapid analysis (20 min), a reliable response even after 60 days of storage and the possibility of miniaturization ( Moço et al, 2019 ).…”
Section: Graphene-based Materials In Virus Sensingmentioning
confidence: 99%
“…Polymeric films are also perfect materials for the conjugation with biomolecules, since they can be chemically functionalized [114]. For instance, polytyramine-conducting polymer with electrochemically reduced graphene oxide (rGO) has been used for the development of new platform for detection of genomic RNA of ZIKV in human serum samples [26]. In this work, ZIKV was quantified via DPV, with LOD down to 0.1 fg/mL, showing good stability and great potential for further practical diagnostic of ZIKV ( Figure 5).…”
Section: Electrochemical Biosensors For Zikv Diagnosticmentioning
confidence: 99%
“…Different materials can improve conductive properties of biosensors and thus increase their sensitivity. Various research groups reported the possibility of functionalization of electrode surfaces by polymeric materials or used them as platforms for ZIKV detection [ 26 , 48 , 56 ]. Polymeric films are also perfect materials for the conjugation with biomolecules, since they can be chemically functionalized [ 114 ].…”
Section: Electrochemical Biosensors For Zikv Diagnosticmentioning
confidence: 99%
See 2 more Smart Citations